2017
DOI: 10.1038/srep40536
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of neofunctionalization after the duplication of the highly conserved Polycomb group gene Caf1-55 in the obscura group of Drosophila

Abstract: Drosophila CAF1-55 protein is a subunit of the Polycomb repressive complex PRC2 and other protein complexes. It is a multifunctional and evolutionarily conserved protein that participates in nucleosome assembly and remodelling, as well as in the epigenetic regulation of a large set of target genes. Here, we describe and analyze the duplication of Caf1-55 in the obscura group of Drosophila. Paralogs exhibited a strong asymmetry in evolutionary rates, which suggests that they have evolved according to a neofunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Nucleotide variation at Caf1-55 in D . subobscura has been previously reported [ 31 ] and sequences are also available in EMBL/GenBank Data Libraries.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide variation at Caf1-55 in D . subobscura has been previously reported [ 31 ] and sequences are also available in EMBL/GenBank Data Libraries.…”
Section: Methodsmentioning
confidence: 99%
“…However, we did detect the losses of esc and Rm64 in more than three specific lineages, taking account of the ancestral states of these genes in the early arthropod phylogeny. The previous study in Diptera showed that the esc/escl duplication took place ß130 million years ago, after the split of the Psychodidae family from other dipteran species (Calvo-Martin et al, 2017). But, the presence of esc/escl in Tardigrada and in a wide range of arthropod species suggested that esc and escl are ancient duplicates, which were already present in the last common ancestor of arthropod species.…”
Section: Phylogenetic Distribution Of Pcg/trxg Genes Across Arthropodmentioning
confidence: 99%
“…Although the fundamental aspect of this regulation mechanism is relevant across different phyla, the evolutionary differences of PcG/TrxG genes between insects and mammals have been identified using a few representative species from plant and bilateral animal kingdoms (Whitcomb et al, 2007). However, most previous studies for arthropod PcG/TrxG genes focused on a few insect species, including D. melanogaster and Bombyx mori, and a comprehensive study providing a global view of PcG/TrxG genes in arthropods has not yet been reported (Schuettengruber et al, 2011;Li et al, 2012;Calvo-Martin et al, 2016;Calvo-Martin et al, 2017). Arthropod genome sequencing initiatives have greatly accelerated the accumulation of genomic resource data of arthropods, which are obtained by using samples from different lineages to explore arthropod genome diversity.…”
Section: Introductionmentioning
confidence: 99%